f ( x ) = x 1 ∫ x x + 2 4 t 2 + 1 d t
Find x → ∞ lim f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Can you elaborate please? @Kushal Bose
Log in to reply
I have updated my solution accordingly .Plz check back and let me know if it is sufficient or not.
L = x → ∞ lim x 1 ∫ x x + 2 4 t 2 + 1 d t = x → ∞ lim d x d ∫ x x + 2 4 t 2 + 1 d t = x → ∞ lim d x d ( ∫ c x + 2 4 t 2 + 1 d t − ∫ c x t 2 + 1 d t ) = x → ∞ lim ( x + 2 4 ) 2 + 1 − x 2 + 1 = x → ∞ lim ( x + 2 4 ) 2 + 1 + x 2 + 1 4 8 x + 5 7 6 = x → ∞ lim x 1 + x 4 8 + x 2 5 7 7 + x 1 + x 2 1 4 8 x ( 1 + x 1 2 ) = x → ∞ lim 2 x 4 8 x = 2 4 L’hopital’s Rule Multiplying through by ( x + 2 4 ) 2 + 1 + x 2 + 1
2nd last step is wrong conceptually.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = x ∫ x x + 2 4 t 2 + 1 d t
Put x = ∞ in both neumerator and denominator..In neumerator evaluate integral by-parts put as limits infinity the value will be tends to infinity.Denominator will also be infinity.
Now differentiate w.r.t. x .For nuemerator use Newton-Liebnitz rule.
f ( x ) = x → ∞ lim 1 ( x + 2 4 ) 2 + 1 − x 2 + 1
Now substitute x = z 1
z → 0 lim z ( 1 + 2 4 z ) 2 + z 2 − z 2 + 1
putting z = 0 in both sides it is in 0 / 0 form .So using L'hospital Rule differentiating w.r.t. x
z → 0 lim 2 ( 1 + 2 4 z ) 2 + z 2 2 ( 1 + 2 4 z ) 2 4 + 2 z − 2 z 2 + 1 2 z
putting z = 0 we get the value 2 4